Income Inequality Analysis and Factors Affecting It (Empirical study of Riau Archipelago Province 2017- 2019) - Devi, Shela Nirmala; Hasmarini, Maulidyah Indira (Prosiding University Research Colloquium, 2022)
Inequality is one of the obstacles in economic development in each region. The difference in income distribution is seen to make the distance between the rich and poor groups even further and the unequal welfare shows that there are still upper and lower classes of society. This study aims to analyze the magnitude of income inequality in the Riau Islands Province with several selected variables, namely: Gross Regional Domestic Product; Number of Poor People; Human Development Index; Open Unemployment Rate. The source of the data used comes from the Central Bureau of Statistics of the Riau Archipelago Province. This study uses theil entropy index analysis method and panel data regression. The model chosen from this research is the Random Effect Model (REM). From the model, it is known that the Gross Regional Domestic Product and the Human Development Index have a significant effect on income inequality in the Riau Islands Province 2017-2019.